Problem solving and programming concepts - Sprankle, Maureen (Pearson Prentice Hall, 2006)
This text covers the basic problem-solving concepts that readers need to know and understand when working in any computer language or application. With detailed explanations and numerous illustrations, this book encompasses all fundamental areas of problem solving from the basics of mathematical functions and operators, to the design and use of such techniques as codes, indicators, control breaks, arrays, pointers, file updates, and report handling. The essential tools of problem solving (including structure charts, IPO charts, algorithms, and flowcharts) are explained and demonstrated extensively throughout, and the text establishes the four basic logic structures: sequential, decision, repetition, and case structures. The text includes coverage of problem solving techniques for horizontal software such as word processing, spreadsheets, and database management systems (book cover)